'Disparate in Voice, Sympathetic in Direction': Gendered Political Blackness and the Politics of Solidarity. Issue 1 (November 2014) - Swaby, Nydia A.
While political blackness seems to be making quite a comeback, this resurgence has also met with frustration and ambivalence. This paper aims to make sense of why this mobilising concept is accepted in some contemporary black feminist circles and outright rejected in others. It unpicks the diasporic dimensions of political blackness, reflecting on the issues that converged to foreground 'black' as the basis for mobilising women of African and Asian decent to engage in collective activism. Attention is given to the Organisation of Women of Asian and African Descent, a national network that linked black women's organisations and expressed and projected what the author defines as gendered political blackness. Interrogating its implications and the tendency towards ideological policing, the author argues that political blackness must be viewed as a politics of solidarity. If it is to maintain its viability, political blackness needs reframing, contextualising and further analysis. A retelling of its ideological underpinnings, and crucially the tensions and contradictions inherent in political blackness, offers a critical lens through which to rethink how we use it as a mobilising tactic in the present.